Praktyczne, zwyczajowe metody wyceny różnego rodzaju działalności, czyli o zastosowaniu rules of thumb w wycenie małych przedsiębiorstw - Zarzecki, Dariusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In the US small businesses to which rule of thumb multipliers apply are typically those with sales in a range of $100 000 and $3 million. The rule of thumb is developed by interpretation of actual market transactions reported by brokers and others involved. Sometimes valuation formulas are traditional rules of thumb used by a particular industry. A comparison of rule of thumb multiplier ranges helps the valuation analyst view how the market perceives relative risk of one industry compared with another. Although the use and composition of rule of thumb formulas may vary depending upon economic conditions or local differences in business customs, formulas provide a reasonably uniform national guide. Formulas are relatively easy to use and make sense to both laymen and professionals. Nevertheless, values estimated by market formulas ought to be validated by other, more rigorous, methods. There are also certain cautions about using rule of thumb formulas: 1) formulas are general in nature; 2) there is no single, all-purpose formula; 3) not all businesses are saleable. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 383-390